Balance impairment in individuals with COPD: a systematic review with meta-analysis. Issue 7 (14th May 2020) - Loughran, Kirsti Jane; Atkinson, Greg; Beauchamp, Marla K; Dixon, John; Martin, Denis; Rahim, Shaera; Harrison, Samantha Louise
Abstract : Background: People with chronic obstructive pulmonary disease (COPD) are four times more likely to fall than healthy peers, leading to increased morbidity and mortality. Poor balance is a major risk factor for falls. This review aims to quantify the extent of balance impairment in COPD, and establish contributing clinical factors, which at present are sparse. Methods: Five electronic databases were searched, in July 2017 and updated searches were performed in March 2019, for studies comparing balance in COPD with healthy controls. Meta-analyses were conducted on sample mean differences (MD) and reported correlations between balance and clinical factors. Meta-regression was used to quantify the association between mean difference in percentage predicted forced expiratory volume in 1 s (FEV1 ) and mean balance impairment. Narrative summaries were provided where data were insufficient for meta-analysis. Results: Twenty-three studies were included (n=2751). Meta-analysis indicated COPD patients performed worse than healthy controls on timed up and go (MD=2.77 s, 95% CI 1.46 s to 4.089 s, p=<0.005), single leg stance (MD=−11.75 s, 95% CI −15.12 s to −8.38 s, p=<0.005) and berg balance scale (MD=−6.66, 95% CI −8.95 to −4.37, p=<0.005). The pooled correlation coefficient between balance and reduced quadriceps strength was weak-moderate (r=0.37, 95% CI 0.23 to 0.45, p=<0.005). The relationship between differences in percentage predicted FEV1 and balance were negligible (r 2 =<0.04). Conclusions: Compared with healthy controls, people with COPD have a clinically meaningful balance reduction, which may be related to reduced muscle strength, physical activity and exercise capacity. Our findings support a need to expand the focus of pulmonary rehabilitation to include balance assessment and training, and further exploration of balance impairment in COPD. PROSPERO registration number CRD4201769041